Effect of PRECEDE-based nursing combined with individualized exercise guidance on pulmonary function and exercise capacity in patients with pulmonary tuberculosis (PRECEDE护理模式配合个体化运动指导对肺结核患者肺功能与运动能力的影响) - CHEN Wumei (陈伍梅); FENG Cuilian (冯翠莲); HUANG Liping (黄丽萍); LI Yongjun (黎拥军); HUANG Danting (黄丹婷); TAN Yuting (谭玉婷) (中西医结合护理)
Objective To investigate the effect of PRECEDE-based nursing combined with individualized exercise guidance on pulmonary function and exercise capacity in patients with pulmonary tuberculosis. Methods Totally 90 patients with pulmonary tuberculosis were randomly divided into the control group and observation group, with 45 cases in each group. The control group received individualized exercise guidance, and the observation group received PRECEDE-based nursing ombined with individualized exercise guidance. The pulmonary function, exercise capacity, quality of life and satisfaction with nursing service were evaluated and compared between two groups. Results The forced expiratory volume in 1 second(FEV1), forced vital capacity (FVC) and FEV1/FVC% were increased in both two groups after intervention, and FEV1, FVC and FEV1/FVC% in the observation group were higher than those in the control group (P＜0. 01). The outcomes of 6-minute walking test (6MWT), 30-seconds sit-to-stand test (STS-30) and 30-second arm curl test(30-ACT) were increased in both two groups after intervention, and outcomes of 6MWT, STS-30 and 30-ACT in the observation group were higher than those in the control group (P＜0. 01). The St George's Respiratory Questionnaire (SGRQ) score were decreased in both two groups after intervention, and SGRQ score in the observation group were lower than that in the control group (P＜0. 01). The satisfaction degree in the observation group was higher than that in the control group(P＜0. 05). Conclusion The PRECEDE-based nursing interventions combined with individualized exercise guidance are effective to improve the pulmonary function, exercise capacity, quality of life and satisfaction of patients with pulmonary tuberculosis. (目的 探讨PRECEDE护理模式配合个体化运动指导对肺结核患者肺功能与运动能力的影响。方法 选择医院2021年10月—2023年4月收治的肺结核患者90例作为研究对象, 按随机数字表法分为对照组和观察组, 各45例。对照组给予个体化运动指导, 观察组给予PRECEDE护理模式配合个体化运动指导。比较两组的护理前后肺功能、运动能力和生活质量相关指标和量表评分变化, 评价患者护理满意度。结果 干预后两组1s用力呼气容积(FEV1), 用力肺活量(FVC)、FEV1/FVC%值均高于干预前, 且观察组高于对照组, 差异有统计学意义(P＜0. 01)。干预后两组6分钟步行试验(6MWT)、30 s坐立试验(30 s-STS)、30 s前臂屈曲试验(30-ACT)值均高于干预前, 且观察组高于对照组, 差异有统计学意义(P＜0. 01)。与干预前相比, 治疗后两组圣乔治呼吸问卷(SGRQ)评分降低, 且观察组低于对照组, 差异有统计学意义(P＜0. 01)。观察组护理满意度高于对照组(P＜0. 05)。结论 与单一个体化运动指导相比, PRECEDE护理模式配合个体化运动指导在提升肺结核患者肺功能、运动能力方面效果更佳, 能够进一步提升患者护理满意度, 改善患者生活质量。)